Performance Evaluation of 5G New Radio Physical Uplink Channels with LDPC and Polar Coding on AWGN Channels - Kumar, Arun; Gaur, Nishant; Chakravarthy, Sumit; Nanthaamornphong, Aziz (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper presents a MATLAB-based simulation for the performance assessment of 5G New Radio’s (NR) Physical Uplink Shared Channel (PUSCH) using Additive White Gaussian Noise (AWGN) and Low-Density Parity-Check (LDPC) and Polar coding. The Modulation and Coding Scheme (MCS) table, as defined in the 3GPP TS 38.214 standard, was manually implemented, with five Quadrature Phase-Shift Keying (QPSK) entries and varying code rates used for simplicity. An array was initialized to compute Bit Error Rate (BER) against a range of Signal-to-Noise Ratio (SNR) values from -10 to 20 dB.